THE IMPLEMENTATION OF GIVING AROMATERAPY LEMONS AND GINGER DRINKS TO REDUCE EMESIS GRAVIDARUM ON PREGNANT WOMEN TRIMESTER I IN BPM YUSIDAH EDWARD PALEMBANG IN 2018 - Rosmiarti Asmar; Aminah Maya; Cica Novitasari (Jurnal Delima Harapan, 2021)
Many pregnant women experience emesis gravidarum in the first trimester. Nausea vomiting can be treated with pharmacological and non-pharmacological treatments, one of which is aromatherapy lemon which has an effect on the inhaler, such as calmness and freshness of the body so that it can reduce nausea and vomiting. In addition, ginger drinks also include non-pharmacological drugs, ginger has a fragrant aroma that can refresh the body ,and the oloresin can warm the body so that it can reduce nausea vomiting. The aim of this study is to find out the application of lemon aromatherapy and ginger drinks to reduce emesis gravidarum in pregnant women and to find out the frequency distribution before and after the application of aromatherpy lemon and ginger drinks to reduce emesis gravidarum trimester I. The method of this study was a one group pre-post-test pre-experiment research and used the Wilcooxon test statistic test. This study obtained interviews through direct observation sheets. The results of administration were given to 15 respondents of lemon aromatherapy and 15 respondents of ginger drinks done twice a day for 3 to 7 days. The amount of nausea and vomiting was taken through average value before and after administration of lemon aromatherapy and ginger drinks. The conclusion of this study is that Aromatherapy lemon and ginger drinks were proven to reduce emesis gravidarum in first trimester pregnant women in Yusidah Edward Palembang BPM in 2018. Hopefully there are some researches that related to other kinds of aromatherapy that useful for pregnancy